About time: The narrowing gender wage gap in Austria - René Böheim; Marian Fink; Christine Zulehner (Johannes Kepler University of Linz, Department of Economics, 2019)
We examine the gender wage gap in Austria from 2005 to 2017 using data from EU-SILC. The raw wage gap declined from 18.6 log points in 2005 to 14.9 log points in 2017. We use standard decomposition techniques that correct for differences in the distributions of human capital, and other variables, between men and women. All calculated decompositions indicate that the unexplained part of the gender wage gap decreased substantially over the last ten years. The decrease of the unexplained gender wage gap between the largest gap in this period (2006) and the most recent gap (2017) ranges from 3.7 log points to 8.5 log points depending on the decomposition approach. Using the approach developed by Neumark (1988), the corrected wage gap shrank from 8.7 (8.8) log points in 2005 (2006) to 5.1 log points in 2017. The main reason for the decline in wage differences is the relative improvement of women's observed and unobserved characteristics.
Keywords: J31; J71; 330; gender wage differentials; wage inequality; decomposition; EU-SILC